Corporate Human Rights Obligations and International Investment Law (2010)
Globalisation has blurred the artificial borders that exist between economies and societies around the world. The activities of corporations in this globalised environment have often served as the catalyst for human rights violations; due to the lack of institutional protection, some corporations are able to exploit regulatory lacunae and the lack of human rights protection. It appears that the paradigmatic change demands an equal emphasis of rights and obligations of corporations. This article discusses and critically analyses corporate human rights obligations and the lack thereof under stabilization clauses in foreign investment contracts. First, stabilization clauses in foreign investment agreements are examined in relation to corporate obligations and responsibility for fundamental human rights. In doing so the substantive and procedural dimension of stabilization clauses is analysed. Second, using the concrete examples of the Mineral Development Agreement between Mittal Steel and the Government of Liberia Mittal Steel Agreement and of the Baku‐Tblisi‐Ceyhan Pipeline Project as case studies, this article considers an application of stabilization clauses in foreign investment contracts in relation to the fundamental human rights obligation of states and of corporations. Third, a proposal for reform in the form of a fundamental human rights clause is introduced. To be clear, the argument here is that the fundamental human rights obligations of investors, particularly of corporations, must be included in foreign investment agreements.